Frisian Land Law: A Critical Edition and Translation of the Freeska Landriucht - Nijdam, Han; Hallebeek, Jan; de Jong, Hylkje (Brill, 2023)
Around 1485, the age-old compilation of Old Frisian customary law, partly dating back to the 11th century, was put into print. Latin glosses were included in the text with references to Canon and Roman law. This gloss tradition had come into being during the 13th and 14th centuries. This incunable came to be known as Freeska Landriucht or Frisian Land Law. This book presents its first edition with an English translation.